Design and Fabrication of an Instrument for Splitted Jute Fiber Length Measurement - Redwanul Islam, Md.; Ara Begum, Hosne; Sharif Ahmed, Md.; Zakir Hossain, H. M.; Fahmida-E-Karim (Asian Journal of Engineering and Applied Technology, 2022)
Fibers are the main raw materials in the textile industry. Now-a-days various types of fibers are available around the world, but all fibers are not textile fibers. Because for being textile fibers, the fibers must have some particular physical and chemical properties. The length of natural fiber plays an important role both in the spinning process and product quality. In this work, it is highlighted about a long staple natural fiber which is called jute fiber. In the 19th century, jute fiber was called the *Golden Fiber* of Bangladesh. After that this fiber lost its name and fame for the cause of our negligence and lack of knowledge. It is very difficult to know about jute because a few people were working on it. Though it’s a long fiber but there are some problems with its fixed length because this fiber consists of a large number of ultimate cells whose length is 1.5 to 4 millimeters, and these cells are attached by lignin which is known as natural cement. A long fiber which is 5 to 10 feet forms after attaching these ultimate cells. During the retting period some of the lignin layers break down and long fiber length of fibers becomes shorter. Another important thing is these fibers have a mesh structure for this reason it’s difficult to identify the actual length of the fibers. That’s why fibers obtained after retting are passed through jute carding machines. The main function of the jute carding machine is to split up and break down the mesh structure. After carding, it’s quite easy to measure the length of splitted jute fibers. There are not any suit-able machines for measuring the length of jute fibers. Previously people use the scale for measuring the jute fibers' length manually, through this it is so difficult to measure the length of the long fibers accurately. Here an instrument has been designed with Arduino UNO, Ultrasonic distance sensor, Image-j software, C-programming and fabricated for measuring the fibers' length easily and accurately as well as this instrument can measure the number of fibers in that particular length. By using this instrument anyone can easily measure the length of the fibers and the number of fibers within a short possible time efficiently.